2016
DOI: 10.1007/s12264-016-0030-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular, Functional, and Structural Imaging of Major Depressive Disorder

Abstract: Major depressive disorder (MDD) is a significant cause of morbidity and mortality worldwide, correlating with genetic susceptibility and environmental risk factors. Molecular, functional, and structural imaging approaches have been increasingly used to detect neurobiological changes, analyze neurochemical correlates, and parse pathophysiological mechanisms underlying MDD. We reviewed recent neuroimaging publications on MDD in terms of molecular, functional, and structural alterations as detected mainly by magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 132 publications
(152 reference statements)
0
40
0
1
Order By: Relevance
“…Confirming earlier reports, we did not find differences in speed of neurocognitive performance in any of the domains (Daban et al, 2012). The specificity in differences in cognitive functioning across the three mood disorder subgroups demonstrates the heterogeneity of mood disorders that has been shown in other domains including biological markers (Glaus et al, 2014; Thase, 2014), structural and functional neuroimaging (Zhang et al, 2016), and treatment response (Karyotaki et al, 2016). …”
Section: Discussionmentioning
confidence: 87%
“…Confirming earlier reports, we did not find differences in speed of neurocognitive performance in any of the domains (Daban et al, 2012). The specificity in differences in cognitive functioning across the three mood disorder subgroups demonstrates the heterogeneity of mood disorders that has been shown in other domains including biological markers (Glaus et al, 2014; Thase, 2014), structural and functional neuroimaging (Zhang et al, 2016), and treatment response (Karyotaki et al, 2016). …”
Section: Discussionmentioning
confidence: 87%
“…Major depression affects the structure, connectivity, and biochemistry of several, especially frontal brain areas implicated in cognitive control, emotion regulation, and memory processing [94]. Several studies have robustly shown evidence of grey matter reduction in the ACC [95][96][97].…”
Section: Depressive Spectrum: Subclinical To Clinicalmentioning
confidence: 99%
“…Furthermore, several genetic variants that influence brain structure have been identified 10,11 . Subcortical brain volume and WM microstructure abnormalities in corticostriatal and limbic networks have also been shown to distinguish individuals with SCZ, BD and MDD from controls in several studies, albeit with some inconsistencies [12][13][14][15][16][17] . Differences between patients and controls in global measures of WM microstructure, diffusion tensor imaging (DTI) biomarkers fractional anisotropy (FA) and mean diffusivity (MD), have been more consistently reported in these disorders [18][19][20][21][22][23] , and could suggest wide-spread WM integrity reductions.…”
Section: Introductionmentioning
confidence: 99%